2009
DOI: 10.1111/j.1529-8027.2009.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic peripheral neuropathy and relation to glycemic control therapies at baseline in the BARI 2D cohort

Abstract: We evaluated the associations between glycemic therapies and prevalence of diabetic peripheral neuropathy (DPN) at baseline among participants in the Bypass-Angioplasty-RevascularizationInvestigation-2-Diabetes (BARI 2D) trial on medical and revascularization therapies for coronary artery disease (CAD) and on insulin-sensitizing versus insulin-providing treatments for diabetes. 2368 patients with type 2 diabetes and CAD were evaluated. DPN was defined as clinical examination score >2 using the Michigan Neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 30 publications
(34 reference statements)
9
71
1
6
Order By: Relevance
“…A population-based study has indicated that neuropathy develops in as many as 50% of all patients with type 1 or type 2 diabetes 187 . Neuropathic pain develops in >30% of these patients, meaning that approximately one in six patients with diabetes develops a painful neuropathy [188][189][190] .…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…A population-based study has indicated that neuropathy develops in as many as 50% of all patients with type 1 or type 2 diabetes 187 . Neuropathic pain develops in >30% of these patients, meaning that approximately one in six patients with diabetes develops a painful neuropathy [188][189][190] .…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…There are several risk factors associated to the development and progression of DSP, among them advanced age, male gender, non-hispanic blacks, longer DM duration, glycosilated hemoglobin (HbA1c) higher than 7%, insulin therapy and history of systemic hypertension (SH), DLP and albuminuria 51 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Hallazgos similares se han encontrado en otros estudios inclusive con frecuencias menores (10,11); sin embargo, también existen estudios que describen frecuencias elevadas hasta de 75% con buenos valores de sensibilidad, especificidad y valores predictivos (12)(13)(14). El amplio de las frecuencias halladas con el uso del MNSI puede deberse a que la frecuencia de los factores de riesgo para NDP como edad, valores de hemoglobina glicosilada, tiempo de enfermedad, fue muy distinta entre estos estudios y solo algunos compararon el MNSI con la VCN (9,12,15).…”
Section: Discussionunclassified